The immune evasion protein Sbi of Staphylococcus aureus occurs both extracellularly and anchored to the cell envelope by binding lipoteichoic acid. - Smith,EJ; Corrigan,RM; van,der Sluis T; Gründling,A; Speziale,P; Geoghegan,JA; Foster,TJ (Mol Microbiol, 2012)
The Sbi protein of Staphylococcus aureus comprises two IgG binding domains similar to those of protein A and a region that triggers the activation of complement C3. Sbi is expressed on the cell surface but its C-terminal domain lacks motifs associated with wall or membrane anchoring of proteins in Gram-positive bacteria. Cell-associated Sbi fractionates with the cytoplasmic membrane and is not solubilised during protoplast formation. S.aureus expressing Sbi truncates of the C-terminal Y domain allowed identification of residues that are required for association of Sbi with the membrane. Recombinant Sbi bound to purified cytoplasmic membrane material in vitro and to purified lipoteichoic acid. This explains how Sbi partitions with the membrane in fractionation experiments yet is partially exposed on the cell surface. An LTA-defective mutant of S. aureus had reduced levels of Sbi in the cytoplasmic membrane.